Interaction of isolated silymarin flavonolignans with iron and copper - Tvrdý, Václav; Catapano, Maria Carmen; Rawlik, Tomasz; Karlíčková, Jana; Biedermann, David; Křen, Vladimír; Mladěnka, Přemysl; Valentová, Kateřina (Journal of inorganic biochemistry, 2018)
Silymarin, the standardized extract from the milk thistle (Silybum marianum), is composed mostly of flavonolignans and is approved in the EU for the adjuvant therapy of alcoholic liver disease. It is also used for other purported effects in miscellaneous nutraceuticals. Due to polyhydroxylated structures and low systemic bioavailability, these flavonolignans are likely to interact with transition metals in the gastrointestinal tract. The aim of this study was to analyze the interactions of pure silymarin flavonolignans with copper and iron. Both competitive and non-competitive methods at various physiologically relevant pH levels ranging from 4.5 to 7.5 were tested. Only 2,3‑dehydrosilybin was found to be a potent or moderately active iron and copper chelator. Silybin A, silybin B and silychristin A were less potent or inactive chelators. Both 2,3‑dehydrosilybin enantiomers (A and B) were equally active iron and copper chelators, and the preferred stoichiometries were mainly 2:1 and 3:1 (2,3‑dehydrosilybin:metal). Additional experiments showed that silychristin was the most potent iron and copper reductant. Comparison with their structural precursors taxifolin and quercetin is included as well. Based on these results, silymarin administration most probably affects the kinetics of copper and iron in the gastrointestinal tract, however, due to the different interactions of individual components of silymarin with these transition metals, the biological effects need to be evaluated in the future in a much more complex study.
Keywords: železo; Molecular Structure; měď; Dehydrosilybin; Silybin; Stereoisomerism; stereoizomerie; Silymarin; Silychristin; Iron; flavonolignany; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; silymarin; GIT; molekulární struktura; Copper; Flavonolignans